2021
DOI: 10.15561/20755279.2021.0501
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between leisure satisfaction, physical activity level and healthy life-style behaviors of sport science students during the COVID-19 pandemic

Abstract: Background and Study Aim. The purpose of the study was to determine the relationship between leisure satisfaction, physical activity levels and healthy life-style behaviors of sport science students during the COVID-19 pandemic in distance education. Material and Methods. In total, 218 sport science students participated in this study voluntarily. The short form of International Physical Activity Questionnaire was administered for the determination of physical activity level of distance education student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Similar to the result of our study, many studies have shown that depression levels are associated with physical activity (Xiang et al 2020;Luo et al 2022;Coughenour et al 2021). Also, there is a relationship between depression level and the sleep quality of individuals (Iyigun et al 2017;Ozkan et al 2015). It increases selfconfidence in individuals thanks to both the physical and mental benefits that physical activity provides.…”
Section: Effects Of Physical Activity On University Studentssupporting
confidence: 87%
“…Similar to the result of our study, many studies have shown that depression levels are associated with physical activity (Xiang et al 2020;Luo et al 2022;Coughenour et al 2021). Also, there is a relationship between depression level and the sleep quality of individuals (Iyigun et al 2017;Ozkan et al 2015). It increases selfconfidence in individuals thanks to both the physical and mental benefits that physical activity provides.…”
Section: Effects Of Physical Activity On University Studentssupporting
confidence: 87%
“…The findings of the current study revealed that the HPLP-II total score of the athlete university students was moderate (130.41 ± 22.93), the highest healthy lifestyle behaviors were spiritual growth and interpersonal relationships, and the lowest behaviors were health responsibility and nutrition. Previous studies in the literature show that Turkish athlete university students had moderate HPLP-II scores, that the highest scores were spiritual growth/self-actualization, interpersonal relationships, and the lowest scores were physical activity, stress management, and nutrition (55,56). In addition, this study also revealed a lowlevel negative correlation between HPLP-II total, physical activity, spiritual growth, interpersonal relationships, stress management scores, and depression scores of the participants.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, sport science students during the pandemic had a medium intolerance level of uncertainty, which also indicates that their behaviors and perceptions are moderate regarding the unknown factors about the future [ 23 ]. Moreover, they were physically active and maintained average scores in healthy lifestyle behaviors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%